Quantum Simulation of Non‐Perturbative Cavity QED with Trapped Ions. Issue 4 (3rd February 2020) - Jaako, Tuomas; Garcia‐Ripoll, Juan José; Rabl, Peter
Abstract: The simulation of non‐perturbative cavity‐QED effects is discussed using systems of trapped ions. Specifically, the implementation of extended Dicke models with both collective dipole‐field and direct dipole–dipole interactions is addressed, which represent a minimal set of models for describing light–matter interactions in the ultrastrong and deep‐strong coupling regime. It is shown that this approach can be used in state‐of‐the‐art trapped ion setups to investigate excitation spectra or the transition between sub‐ and superradiant ground states, which are currently not accessible in any other physical system. The analysis also reveals the intrinsic difficulty of accessing this non‐perturbative regime with larger numbers of dipoles, which makes the simulation of many‐dipole cavity QED a particularly challenging test case for future quantum simulation platforms. Abstract : In this work, a trapped‐ion simulation of the extended Dicke model is proposed, which represents a minimal model for light–matter interactions in the ultrastrong coupling regime. Already with existing ion traps, this approach can be used to investigate few‐dipole excitation spectra or the transition between sub‐ and superradiant ground states, which are currently not accessible in any other experimental setting.